Localization of the glycoprotein Cb42 in larvae of the screwworm fly Chrysomya bezziana (Diptera: Calliphoridae) - Eisemanni, Creig; Muharsini, Sri (Indonesian Animal Sciences Society, 2000)
The glycoprotein Cb-peritrophin-42 was localized in third instar larvae of Chrysomya bezziana using primary antibodies raised against a non-glycosylated bacterial recombinant form of this protein. Both immunofluorescent antibody techniques on unfixed whole mounts of gut tissues and immunogold electron microscopy techniques on ultra-thin sections of fixed and embedded tissues were employed. The protein was shown to be exposed over the whole of both surfaces of the peritrophic membrane and to occur throughout its thickness. Immunogold labelling indicated that Cb-peritrophin-42 was expressed in the peritrophic membrane-secreting cells of the cardia, a specialized peritrophic membrane-forming organ situated at the junction of the foregut and midgut. The accessibility of Cb-peritrophin-42 present in intact peritrophic membrane to the primary antibodies used in the immunofluorescent antibody localization indicates that this glycoprotein is a potential molecular target for vaccination of host animals against larvae of Chrysomya bezziana. Â Key words: Cb-peritrophin-42, Cb42, glycoprotein, peritrophic membrane, immunolocalization